Sistema de control interno administrativo y financiero para la caja solidaria "unión y progreso" La Calera, de la Parroquia Eloy Alfaro, Cantón Latacunga, Provincia De Cotopaxi - Cunuhay Chusin, Alexandra Paulina (2019)
This project is based on the development of an internal administrative and financial control system for La Calera Common Fund Union and Progreso, aimed at strengthening the organization and making appropriate decisions, as a result of the weaknesses found in the administrative and financial area due to the inadequate application of internal processes that impedes the effective fulfillment of functions within the organization. To handle and analyze the information, a qualitative approach is used which will allow the approach to the operation of the common fund through its characteristics, administrative and financial components, through the application of interviews and checklist whose results become inessential information; additionally to the documentary research to integrate a base of documents related to the problem. This is integrated to direct observation with the purpose of verifying the operation of the common fund and the behavior of the internal components according to the financial activities it performs.The result of the project was achieved through the situational analysis of the institution to identify its deficiencies at an administrative and financial level, and in this way obtain the basis for the development of the proposal. This is accompanied by the structuring of the control manual which contains the processes carried out by the organization that is complemented by rules and policies which will improve the supervision of internal activities. A final result is a tool capable of being applied to the development the context of La Calera common fund Union and Progreso, thus getting the control of its activities a significant improvement of the internal functioning and in this way to extend its attention capacity, trying to increase the quality of life in the community. Moreover, with these components, the basis for the socialization of the system is established which must be exposed to the whole entity.